Evaluation of the Potential of Fungal Biopesticides for the Biological Control of the Seed Bug, Elasmolomus pallens (Dallas) (Hemiptera: Rhyparochromidae) - Umaru, Fredrick Fidelis; Simarani, Khanom (MDPI, 2020)
Elasmolomus pallens is a post-harvest insect pest of groundnuts which causes severe yield loss to farmers, particularly in Africa and Asia. Resistance to synthetic chemicals has been on the rise among insects and is a constraint on insecticides regulations. In view of the drive for alternative approaches to synthetic insecticides, this study evaluated the potential of biopesticides based on entomopathogenic fungi against E. pallens under laboratory conditions. Fungal isolates from the bug cadaver including Fusarium proliferatum F1, Aspergillus tamarii F2, A. flavus F3, Trichoderma atroviride F4, A. niger F4, and Metarhizium anisopliae (Meschn.) Sorokin, originating from the cadaver of Zonocerus variegatus were screened for virulence against the bug. Adult bugs were dipped briefly in conidial concentration 1 × 108 conidial mL−1 and observed at 25 ± 2 °C, 80 ± 10 RH and 14: 10 L:D for 10 days. The fungal isolates caused mortality ranging from 48 to 100% based on their potential to infect and kill the bug. Five conidial concentrations (1 × 104 to 1 × 108 conidia mL−1) were evaluated against adult bugs in the multiple-dose virulence bioassay. Lethal concentrations (LC50 and LC90) values of 6.75 × 106 and 4.42 × 109 conidia mL−1 were obtained for A. flavus F3 while M. anisopliae had 8.0 × 106 and 6.14 × 108 conidia mL−1 respectively. Lethal time (LT50 and LT90) values were 3.3 and 6.2 days for A. flavus F3 compared to 3.6 and 5.6 days for M. anisopliae, respectively. Thus, A. flavus F3 showed potential against E. pallens; and can be considered as an ideal isolate for incorporation into formulations for field applications. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.